(untitled) (Research, Society and Development, 2024)
Endometritis is one of the main causes of infertility in mares and is characterized by inflammation of the uterine endometrium, usually caused by bacteria such as Streptococcus zooepidemicus and Escherichia coli or by fungi. The aim of this study is to review the management of chronic infectious and degenerative endometritis in mares, addressing the pathogens involved, diagnostic methods, treatments and new therapies. The methodology used involved a narrative review of the literature, searching databases such as Google Scholar, PubMed and Scielo, as well as regulations from organizations such as the OIE. The results highlight the complexity of chronic endometritis, which can be infectious, caused by bacteria and fungi, or degenerative, as in chronic endometriosis, which affects fertility irreversibly. Diagnosis is made using bacterial culture, cytology and biopsy of the uterus. Treatment includes the use of antibiotics and antifungals, as well as uterine washings to remove secretions. Recently, alternative therapies, such as immunomodulators and probiotics, have been studied to combat antimicrobial resistance and improve the local immune response. Endometritis represents a significant challenge in equine reproduction, especially in chronic cases. Integrating traditional treatments with innovative approaches can improve the chances of reproductive success, but more studies are needed to assess the long-term effectiveness of these therapies.